Determination of Auditor Experience, Task-Specific Knowledge, and Implementation of Institution Governance Against Fraud Prevention - Agus Joko (Pandawan, 2023)
This type of qualitative descriptive research. The population of the BPK RI office is 30 respondents. The data analysis technique used in this research is Confirmatory Factor Analysis (CFA). Factor analysis is one of the multivariate statistical techniques used to summarize (data summarization) and reduce data (data reduction) from a large number of variables into a smaller number. The results of data processing and data analysis, the results obtained that the factors that influence Fraud Prevention are based on their formation, only two factors whose diagonal value is above 0.5, it is sufficient to represent the two factors formed which are the factors that affect the Fraud Prevention, namely Auditor Experience and Task-Specific Knowledge